Multi-criteria decision-making model to assess the sustainability of girders and trusses: Case study for roofs of sports halls. (10th March 2020) - Josa, I.; Pons, O.; Fuente, A. de la; Aguado, A.
Abstract: The first, and probably the most determining, decision that engineering teams need to make when facing the structural design of any infrastructure is the choice of both an appropriate material and the suitable structural typology for its components. Each component is required to satisfy technical and functional aspects imposed by standards and stakeholder. Currently, the aspects that are most frequently considered in decision-making processes are economic. Nevertheless, environmental and social criteria are also required if one aims at making sustainability-based decisions. In this regard, to the best of the authors' knowledge, very few tools or studies exist that can support decision-makers. The few that do exist, are rather limited, either because they fail to incorporate many relevant factors in the sustainability assessment of a project or because they only evaluate environmental and social impacts of a project as a whole. Although a global assessment is useful to gain a holistic understanding of impacts of a project and to compare them to other projects, it does not necessarily help engineering teams understand the impact of fundamental decisions made when designing individual structural components. Therefore, the aim of the present research paper is to develop a new method for the sustainability analysis of building structural components which has been specifically oriented to beams and girders. This is done by means of the Integrated Value Model for the Evaluation of Sustainability method, which is known by its Spanish acronym, MIVES ( Modelo Integrado de Valor para una Evaluación Sostenible) . This method draws on multi-attribute utility theory and that allows building an integrated value model as an approach for multi-criteria decision-making. The developed model has been applied to assess the sustainability of different alternatives of beams and trusts to support the non-accessible roof of a sports hall in Vila-seca, Spain. Different material types and structural typologies are analysed. The findings show that the most sustainable alternatives are timber and reinforced concrete trusses, which are actually two options that are seldom used in practice. Highlights: A model to evaluate the sustainability of structural elements is developed. MIVES is proved to be an adequate sustainability assessment tool in these cases. Girders and trusses made of timber, concrete and steel are analysed. Timber and concrete trusses achieve the highest global sustainability indexes.